Capacity Building for Tahfizh Instructors: Developing Structured Lesson Plans for Quality Al-Qur'an Education - Ida Kusumawati; Rifka Jannatul Firdausiyah; Ittaqillah Haisuma Kunta; Hefniy Hefniy; Annisa Tri Ananda Dewi (Al-Qalam Institute, 2026)
This mentoring activity aimed to improve the quality of Al-Qur'an memorisation learning by preparing and implementing the Tahfizh Lesson Plan (RPP) at the Madrasah. The main problem addressed was the lack of structured tahfizh learning tools, which led to less focused learning activities and to memorization outcomes being measured unsystematically. This activity employed a descriptive qualitative method with a participatory strategy involving teacher mentoring, classroom observation, documentation, and pretest-posttest activities with 25 students in the tahfizh program. The results showed improvements in students' memorization ability, recitation discipline, and consistency in muroja'ah. In addition, teachers demonstrated greater readiness, confidence, and competence in managing tahfizh learning, as evidenced by the prepared lesson plan. These findings indicate that a well-structured Tahfizh Lesson Plan can serve as a sustainable learning tool to guide teachers and improve the effectiveness of memorization activities. The implication of this activity is the need for consistent implementation of the Tahfizh RPP and continuous teacher mentoring, which can be replicated in other madrasas to strengthen the quality of Al-Qur'an memorization learning.